Density effects on life-history traits in a wild population of the great tit Parus major: analyses of long-term data with GIS techniques. - Wilkin, T; Garant, D; Gosler, A; Sheldon, B (2006)
1. Population density often has strong effects on the population dynamics and reproductive processes of territorial animals. However, most estimates of density-dependent effects use the number of breeding pairs per unit area in a given season and look for correlations across seasons, a technique that assigns the same density score to each breeding pair, irrespective of local spatial variation. 2. In this study, we employed GIS techniques to estimate individual breeding densities for great tits breeding in Wytham Woods UK, between 1965 and 1996. We then used linear mixed modelling to analyse the effect of density on reproductive processes. 3. The areas of Thiessen polygons formed around occupied nestboxes were used to approximate territory size (necessarily inverse of breeding density). There were significant, independent and positive relationships between clutch size, fledging mass and the number of offspring recruited to the population, and territory size (all P < 0.001), but no effect of territory size on lay-date or egg mass. 4. Thiessen polygons are contiguous and cover all of the available area. Therefore, at low nest densities territory polygons were excessively oversized. Using a novel procedure to address this limitation, territory sizes were systematically capped through a range of maxima, with the greatest effect in the models when territories were capped at 0.9-2.3 ha. This figure approximates to the maximum effective territory size in our population and is in close agreement with several field-based studies. This capping refinement also revealed a significant negative relationship between lay-date and territory size capped at 0.9 ha (P < 0.001). 5. These density-dependent effects were also detected when analyses were restricted to changes within individual females, suggesting that density effects do not merely result from either increased proportions of low-quality individuals, or increased occupation of poor sites, when population density is high. 6. Overall, these results suggest that, in the current population, great tits with territories smaller than c. 2 ha independently lay smaller and later clutches, have lighter fledglings, and recruit fewer offspring to the breeding population. These analyses thus suggest a pervasive and causal role of local population density in explaining individual reproductive processes.